Clinical Characteristics and Risk Factors Associated With Acute Kidney Injury Inpatient With Exertional Heatstroke: An Over 10-Year Intensive Care Survey - Wu, Ming; Wang, Conglin; Liu, Zheying; Zhong, Li; Yu, Baojun; Cheng, Biao; Liu, Zhifeng (Frontiers in Medicine, 2021)
Background: Exertional heat stroke (EHS) is a life-threatening injury that can lead to acute kidney injury (AKI). The clinical characteristics of and risk factors for EHS complicated with AKI have been poorly documented. Methods: A retrospective study with severe EHS admitted to the intensive care unit (ICU) from January 2008 to June 2019 was performed. Data including baseline clinical information at admission, total cost of hospitalization, main organ dysfunction and 90-day mortality were collected. Results: A total of 187 patients were finally included, of which 82 (43.9%) had AKI. AKI patients had more severe organ injury and higher total hospitalization costs than non-AKI patients. Multivariate logistic analysis showed that lymphocyte, neutrophil, D-dimer and myoglobin ≥ 1000ng/ml were independent risk factors for AKI caused by severe EHS. In addition, SOFA score (hazard ratio [HR] 4.1, 95% confidence interval [95% CI] 1.6-10.8, P = 0.004) and GCS score (HR 3.2, 95% CI 1.2-8.4 P = 0.017) were the risk factor for 90-day mortality in patients with severe EHS complicated with AKI, with an area under the curve (AUC) of 0.920 (95% CI 0.842-0.998, P<0.001) and 0.851 (95% CI 0.739-0.962, P<0.001) respectively. Survival analysis showed that the 90-day mortality in AKI patients was significantly high (P<0.0001) and the mortality rate of patients with AKI stage 2 was the highest than other stages. Conclusions: Severe EHS complicated with AKI is associated with higher hospitalization costs and poorly clinical outcomes. MB≥1000ng/ml, Inflammation, coagulation were associated with the occurrence and development of AKI. Early treatment strategies based reducing the SOFA and GCS score may be pivotal for improving the prognosis of severe EHS.